2014
DOI: 10.1186/1471-2253-14-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential side effect of propofol and sevoflurane for anesthesia of anti-NMDA-R encephalitis

Abstract: Background: Many anesthetic drugs interact with the NMDA receptor and may therefore alter the clinical presentation of anti-NMDA-R encephalitis. Case presentation: A 24-year-old woman was admitted to hospital for decreased consciousness and hyperthermia. Cerebrospinal fluid analysis revealed lymphocytic pleocytosis, and elevated protein. Cultures were negative. Patient state worsened with agitation, facial dyskinesia, ocular deviation, and limb dystonia. Diagnosis of anti-NMDA-R encephalitis was evidenced by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…In perioperative treatment to reduce OIH, propofol may have preventive effects (Potter and Moon 2015). However, sevoflurane also involved anti-NMDA receptors in a dose-dependent manner (Lapébie et al 2014). At clinically applied concentrations, the effect of sevoflurane on hyperalgesia is insufficient to prevent that of high-dose remifentanil, and hyperesthesia can be induced by noxious stimulation (Richebé et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In perioperative treatment to reduce OIH, propofol may have preventive effects (Potter and Moon 2015). However, sevoflurane also involved anti-NMDA receptors in a dose-dependent manner (Lapébie et al 2014). At clinically applied concentrations, the effect of sevoflurane on hyperalgesia is insufficient to prevent that of high-dose remifentanil, and hyperesthesia can be induced by noxious stimulation (Richebé et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, remifentanil binds μ receptor and activates active G protein to induce hyperalgesia. Activation of the NMDA receptor system may be one of the main mechanisms for acute tolerance and/or hyperalgesia (Kaye et al 2014). Remifentanil can enhance NMDA receptor function by promoting the expressions of NR2B subunits in spinal cord neurons, and facilitate pain signal transduction and central sensitization, finally resulting in hyperalgesia.…”
Section: Introductionmentioning
confidence: 99%
“…17 Lapebic et al hypothesized that in anaesthesia combining propofol and sevoflurane simultaneously worsen the clinical presentation of anti NMDA receptor encephalitis by facilitating the inhibition of the NMDA pathway. 18 However most cases, did not provide a detailed anaesthetic procedure, and did not describe the postoperative course. Therefore, there is a requirement for additional studies to decide on the choice of anaesthetics for patients with anti-NMDAR encephalitis.…”
Section: Pathological Discussionmentioning
confidence: 99%
“…9 It is reported that propofol, of which the primary effect is produced by enhancing GABAergic transmission, can also act on NMDA receptors and may produce potential side effect in patients with anti-NMDA receptor encephalitis. 3 In order to decrease the dose of propofol during anesthesia, we co-administered benzodiazepines, opiates, and dexmedetomidine (for the second case) under the guidance of bispectral index monitoring.…”
Section: Case Description Casementioning
confidence: 99%
“…2 Since its first denomination by Dalmau et al, 1 many scientific publications have emerged on anti-NMDA receptor encephalitis, but only a few focused on the anesthetic management of patients with this disease. [3][4][5] Herein we reported two cases with anti-NMDA receptor encephalitis in association with ovarian teratoma and discussed the anesthetic management and the outcomes of these patients.…”
mentioning
confidence: 98%